2018
DOI: 10.3390/v10020069
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis Involvement in Transport System and Endothelial Permeability of Vascular Leakage during Dengue Virus Infection

Abstract: The major role of endothelial cells is to maintain homeostasis of vascular permeability and to preserve the integrity of vascular vessels to prevent fluid leakage. Properly functioning endothelial cells promote physiological balance and stability for blood circulation and fluid components. A monolayer of endothelial cells has the ability to regulate paracellular and transcellular pathways for transport proteins, solutes, and fluid. In addition to the paracellular pathway, the transcellular pathway is another r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 88 publications
1
16
0
3
Order By: Relevance
“…A recent study in plasma proteome using proteomics and cytokine profiling in dengue patients showed that an elevated level of IL‐1 RA, IL‐17, TNF‐α, MCP1‐MCAF, and MIP‐1β was observed only in the plasma of DHF patients . Previous studies of DENV2 infection on EA.hy926 cells reported transcellular transport to be affected rather than paracellular transport, whereas paracellular transport was observed to be profound in the cells treated with DENV2 and TNF‐α in the present study . This finding also supported our finding that the synergistic effect of DENV2 and TNF‐α plays a role in the dysfunction of human ECs.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study in plasma proteome using proteomics and cytokine profiling in dengue patients showed that an elevated level of IL‐1 RA, IL‐17, TNF‐α, MCP1‐MCAF, and MIP‐1β was observed only in the plasma of DHF patients . Previous studies of DENV2 infection on EA.hy926 cells reported transcellular transport to be affected rather than paracellular transport, whereas paracellular transport was observed to be profound in the cells treated with DENV2 and TNF‐α in the present study . This finding also supported our finding that the synergistic effect of DENV2 and TNF‐α plays a role in the dysfunction of human ECs.…”
Section: Discussionsupporting
confidence: 92%
“…TNF-α related apoptosis inducing ligand (TRAIL), a type II transmembrane protein belonging to the TNF superfamily, has been shown to contribute to the induction of apoptosis in several types of tumor or virus-infected cells [35,48,49]. Moreover, TNF-α has been shown to enhance vascular hyperpermeability in dengue hemorrhagic fever [27,50]. This study showed that TNF-α mRNA up-regulated in the persistent EEHV4-infected calves suggesting that during EEHV infection, TNF-α not only contributed to apoptosis of the EEHV-infected cells, but also enhanced transmigration of leukocytes out of the blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to peripheral tissues, the rate of transcytosis at the BBB is unusually low. However, this rate may be augmented by increased Src kinase activity, which is mediated by a group of pathological and nonpathological stimuli, including inflammatory mediators and immune cell interactions with brain endothelium (41). Viruses may also increase vesicular trafficking, as has been observed in peripherally derived endothelial cells exposed to dengue virus (42).…”
Section: Discussionmentioning
confidence: 99%